Associations between diet and incidence risk of lung cancer: A Mendelian randomization study - Yan, Haihao; Jin, Xiao; Zhang, Changwen; Zhu, Changjun; He, Yucong; Du, Xingran; Feng, Ganzhu (Frontiers in Nutrition, 2023)
Background: Observational studies have revealed associations between diet and lung cancer. However, it is unclear whether the association is disturbed by confounding factors. We used a two-sample Mendelian randomization (MR) method to characterize the associations between diet and the lung cancer risk (including 3 subtypes: lung adenocarcinoma (LA), squamous cell lung carcinoma (SqCLC), and small cell lung cancer (SCLC)). Materials and methods: Data on 20 diets were screened from the UK Biobank. Lung cancer data came from a large meta-analysis of 85,716 individuals. The inverse-variance weighted method was used as the main analysis. Sensitivity analysis was also used to explain the different multiplicity patterns of the final model. Results: Our results showed significant evidence that 3 diets were associated with lung cancer [odds ratio (OR): 0.271, 95% confidence interval (CI): 0.150–0.488, p = 1.46 × 10-4, dried fruit; OR: 3.010, 95% CI: 1.608–5.632, p = 5.70 × 10-4, beer] and SqCLC (OR: 0.135, 95% CI: 0.062–0.293, p = 2.33×10-5, dried fruit; OR: 0.485, 95% CI: 0.328–0.717, p = 2.9×10-4, cheese). There was also a suggestive correlations between 5 dietary intakes and lung cancer (OR: 0.441, 95% CI: 0.250–0.778, p = 0.008, cereal; OR: 2.267, 95% CI: 1.126–4.564, p = 0.022, beef), LA (OR: 0.494, 95% CI: 0.285–0.858, p = 0.012, dried fruit; OR: 3.536, 95% CI: 1.546-8.085, p = 0.003, beer) and SCLC ( OR: 0.006, 95% CI: 0.000–0.222, p = 0.039, non-oily fish; OR: 0.239, 95% CI: 0.086–0.664, p = 0.006, dried fruit ). No other association between diet and lung cancer was observed. Conclusion: Our study preliminary found that cheese, dried fruit, and beer intake were significantly associated with the risk of lung cancer or its subtypes, while cereal, beef, and non-oily fish intake were suggestively associated with the risk of lung cancer or its subtypes. Well-designed prospective studies are still needed to confirm our findings in the future.